Pour une étude généalogique de la valeur des droits de l’homme : une opposition à l’historicisme et au racisme - Balagué, Laurent (Labyrinth, 2019)
For a genealogical study of the value of human rights: an opposition to historicism and racism The purpose of this article is to focus on human rights as a value in itself that has to fight against other values. We would like to show that human rights have become an intrinsic value only by following a path in human history that distinguish them from historicism. Because human rights became a value through history, it is important to be able to show the lay out of this history. We will illustrate it by means of diverse philosophical theories. We will begin with Leo Strauss' philosophy of natural rights which considers human rights in their opposition to historicism. Then, with the help of Michel Foucault's genealogy we will show how human rights develop themselves against the racist theory elaborated by a fraction of the French aristocracy in the 17th century. Consequently, a tension emerges inside those rights between their natural value and their historical one, which leads to the fundamental question: what is the essence of humankind involved in human rights?